(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
This study presents an analysis of allergic clinical signs in patients with HIV infection accompanied by giardiasis and blastocystosis. 170 HIV-infected patients with intestinal parasitosis - giardiasis and blastocystosis - were diagnosed, and 33 HIV-uninfected patients with laboratory diagnosis of giardiasis and blastocystosis formed the control group. 30 HIV-infected patients with intestinal parasitosis without laboratory diagnosis formed a separate control group. A total of 233 patients formed the study groups. This study used general clinical: patient complaints, anamnesis and objective; laboratory: coproovoscopy, serological and molecular genetic methods. Allergopathologies and the rapid development of allergic processes are one of the main manifestations of HIV infection with intestinal parasitosis (giardiasis, blastocystosis), and this condition is more common in HIV infection with blastocystosis than in giardiasis.